Efektivitas dan Tantangan Kebijakan Hukum Pidana Korupsi: Perbandingan Indonesia, Singapura, Hong Kong, dan Malaysia - Qadriah, Fauza; Ramadi, Bagus; Aminudin, Aminudin (JUNCTO: Jurnal Ilmiah Hukum, 2025)
This article aims to analyze the criminal law policy in handling corruption cases in Indonesia both normatively and empirically, as well as to conduct a comparative study with several other countries. The research adopts a normative legal approach through literature review and secondary data analysis, supported by an empirical examination of the effectiveness of law enforcement. The findings indicate that Indonesia has a comprehensive anti-corruption criminal legal framework, severe sanctions, and specialized institutions such as the Corruption Eradication Commission (KPK). However, the country still faces challenges in implementation, including overlapping authorities among law enforcement agencies, lack of institutional independence, and a deeply rooted culture of corruption. Comparisons with other countries reveal that the key factors in successful anti-corruption policies are strong political will, consistent and impartial law enforcement, an independent judiciary, and a deeply embedded anti-corruption culture. Based on this analysis, the study recommends strengthening the independence of the KPK, enhancing coordination among law enforcement agencies, improving the legal framework, and reforming bureaucratic culture to increase the effectiveness of corruption prevention and eradication efforts in Indonesia.